GENDER, ACADEMIC QUALIFICATION AND SUBJECT DISCIPLINE DIFFERENTIALS OF NIGERIAN TEACHERS’ ICT LITERACY LEVEL - Agbatogun, Alaba Alaolukotansibe (Sokoto Educational Review, 2020)
This study x-rayed the level of ICT literacy as influenced by gender, academic qualification and subject-discipline among public secondary school teachers in Ogun-State, Nigeria. 364 (129 males and 235 females) teachers constituted the sample of this study. The sample has a Mean Age of 35.7 and Standard Deviation of 9.51. Teachers’ Computer Ability Scale (TCAS) with Cronbach coefficient alpha of 0.83 was used for the collection of the data that was analysed with t-test and Analysis of Variance. The study revealed that academic qualification and gender have no influence on the secondary school teachers’ level of ICT literacy, while teacher’s level of ICT literacy was found to be subject discipline determined. It was recommended amongst other things that ministries of education should sensitize all teachers on the relevance of ICT to improved and quality education. Furthermore, government was also encouraged to motivate and sponsor teachers for ICT skills’ acquisition training.